2021
DOI: 10.7759/cureus.18203
|View full text |Cite
|
Sign up to set email alerts
|

Association of Plasma Omentin-1 Levels With Diabetes and Its Complications

Abstract: Introduction: Plasma omentin-1 is a relatively new biomarker that has anti-diabetogenic and its level is inversely related with insulin resistance and diabetes mellitus, thus, increasing the risk of diabetic complications. In this study, we will determine the association between serum plasma omentin-1 levels and diabetes and its complications.Methods: This case control study was conducted from July 2020 to August 2021 in the internal medicine unit of a tertiary care hospital in Pakistan. There was a total of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 16 publications
0
9
0
Order By: Relevance
“…Omentin-1 increased Akt phosphorylation in the insulin signaling pathway in the absence and presence of insulin [ 77 ]. In human studies, serum omentin-1 concentrations were lower in obese patients and inversely correlated with the markers of obesity [ 78 ], metabolic syndrome [ 79 ] and diabetic complications [ 80 ]. Low omentin-1 level has been suggested to be a reliable marker to predict the development of MetS in patients with hypertension [ 81 ].…”
Section: Role Of Novel Adipokines In Non-diabetic Obesitymentioning
confidence: 99%
“…Omentin-1 increased Akt phosphorylation in the insulin signaling pathway in the absence and presence of insulin [ 77 ]. In human studies, serum omentin-1 concentrations were lower in obese patients and inversely correlated with the markers of obesity [ 78 ], metabolic syndrome [ 79 ] and diabetic complications [ 80 ]. Low omentin-1 level has been suggested to be a reliable marker to predict the development of MetS in patients with hypertension [ 81 ].…”
Section: Role Of Novel Adipokines In Non-diabetic Obesitymentioning
confidence: 99%
“…The plasma level of omentin-1 is negatively associated not only with diabetes but its complications as well. A 2021 case-control study showed that patients with diabetes had significantly lower omentin levels in comparison to patients without diabetes, but also that its level was significantly lower in patients with complications than in those without [29]. Serum omentin-1 can be used as a biomarker for obesity-related metabolic disorders because, according to the research, omentin-1 is inversely related to obesity, insulin resistance, and systolic blood pressure (SBP) [30].…”
Section: Characteristics Of Omentin-1mentioning
confidence: 99%
“…Another novel adipokine was identified from omental adipocytes known as omentin-1 or intelectin-1 (10) . Moreover, Eimal Latif et al revealed that omentin is expressed selectively in mesothelial cells, visceral fats, vascular cells, small intestine, colon, and goblet cells and is abundantly present in plasma (11) , As Habi attributed these widespread expressions of omentin in such critical areas to the roles of this peptide to a variety of physiological functions like cardiovascular function, insulin action and inflammatory response (1) . Omentin-1 has also been demonstrated to have the capacity to modify insulin sensitivity (1) and promote the relaxation of vascular smooth muscle cell s (12) .…”
Section: Introductionmentioning
confidence: 99%
“…However, another study discovered that diabetic patients had higher levels of omentin-1 than non-diabetics patients (13) . In addition, recent clinical investigations have found a negative correlation between plasma levels of omentin and oxidative stress, which is considered a possible signal for lowering oxidative stress-related complications in diabetes (11) .…”
Section: Introductionmentioning
confidence: 99%